Association between O-GlcNAc transferase activity and major adverse cardiovascular events: findings from the China PEACE-MPP cohort - Wei Yu; Shiyun Hu; Xiaoling Xu; Jianlin Shao; Jing Yan; Fang Ding (BMC Cardiovascular Disorders)
Abstract Background The O-GlcNAc transferase (OGT) levels are closely related to the O-GlcNAcylation of proteins and are also associated with cardiovascular disease. This study explored the association between OGT activity and major adverse cardiovascular events (MACEs) in patients with high cardiovascular disease risk. This post hoc study included patients from the China PEACE-MPP study in Yi Wu, Zhejiang Province, between 2014 and 2015. Methods The patients were divided into the low and high OGT activity groups according to the median serum OGT value. The outcome was the occurrence of MACEs (cardiovascular death, non-fatal acute myocardial infarction, and non-fatal ischemic stroke). Results Finally, 1947 participants (973 and 974 with low and high OGT activity, respectively) were included. The mean follow-up was 5.56 ± 1.01 years. The participants in the low OGT activity group had a significantly higher occurrence rate of MACEs compared with the high OGT activity group (100 [10.4%] vs. 74 [7.6%], P = 0.032). The Kaplan-Meier analysis showed that the event-free survival rate in the low OGT activity group was significantly lower than in the high OGT activity group (P = 0.036). Multivariable Cox proportional hazards regression analysis showed that after adjustment for age, drinking, hyperglycemia, history of hypertension, and history of cardiovascular and cerebrovascular disease, a high OGT activity was independently associated with a lower risk of MACEs (HR = 0.738, 95%CI: 0.547–0.997, P = 0.048). Conclusions A low OGT activity was independently associated with an increased risk of MACE among patients with a high risk of cardiovascular disease. Trial registration Not applicable.